Software Based Geotechnical Analysis of Spillway Slope Reinforcement - Fabyanto, Ikhsan; Zaki, Muhammad; Pontan, Darmawan; Widiarso, Tulus (Technomedia Journal, 2025)
The construction of large-scale infrastructure such as dams requires precise planning and implementation to ensure structural stability and long-term operational safety. This study aims to analyze slope protection and embankment reinforcement at the spillway excavation area of the Dam Project in Surian District, located in the 137 km-long Cipunagara River Basin. A quantitative approach was applied, using geotechnical modeling software Plaxis 8.6 and Microsoft Excel for data processing. Three slope reinforcement methods were compared: geomat, shotcrete, and cocomesh. Based on the analysis, slope reinforcement using shotcrete achieved the highest safety factor, with short-term SF = 1.649 (34.50% increase) and long-term SF = 1.514 (23.49% increase). Geomat ranked second with SF = 1.544 (25.94%) and 1.418 (15.66%), while cocomesh obtained SF = 1.540 (25.61%) and 1.355 (10.52%). The unreinforced slope had an SF of 1.226. In terms of cost, shotcrete was the most expensive at IDR 4,331,068,967.23, followed by geomat (IDR 2,734,025,024.50) and cocomesh (IDR 906,745,000.00). However, shotcrete also required the longest construction time (30 days) compared to geomat (20 days) and cocomesh (16 days). Shotcrete provides the best technical performance for slope stability, but geomat and cocomesh are more efficient alternatives in terms of cost and time, offering a balanced solution for slope reinforcement projects.